Saturday, 16 JUNE 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.5897
|View full text |Cite
|
Sign up to set email alerts
|

SAT0244 Impact of 12 weeks of upadacitinib treatment on individual and composite disease measures in patients with rheumatoid arthritis and inadequate response to conventional synthetic or biologic dmards

Abstract: Background:Upadacitinib (UPA), an oral, JAK1-selective inhibitor, demonstrated efficacy through 12 and 24 weeks (wks) in phase 3 trials of patients (pts) with active rheumatoid arthritis (RA) and inadequate response (IR) to csDMARDs and bDMARDs, respectively.1,2 Efficacy evaluations at Wk 12 are an important assessment point according to T2T recommendations.3 Objectives:To assess the impact of UPA at 12 wks on individual and composite measures of RA disease activity.Methods:Pts received UPA 15 mg or 30 mg once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of SELECT‐BEYOND study in RA patients that does not respond to bDMARD was similar with the data introduced in SELECT‐NEXT, which administration of upadacitinib caused to fast and meaningful improvements in responses that approached normative values or PROs over 12 weeks (Genovese, Fleischmann, et al, 2018; Strand, Schiff, et al, 2018). Therefore, upadacitinib treatment in RA subjects with poor response to either csDMARDs or bDMARDs exhibited favorable effects compared with patients receiving placebo (FitzGerald et al, 2018; van Vollenhoven et al, 2018). An open‐label extension study also demonstrated that efficacy responses last up to 72 weeks in RA patients on 6 mg BID upadacitinib (Genovese, Kremer, Zhong, & Friedman, 2018).…”
Section: Clinical Developmentsmentioning
confidence: 99%
“…The results of SELECT‐BEYOND study in RA patients that does not respond to bDMARD was similar with the data introduced in SELECT‐NEXT, which administration of upadacitinib caused to fast and meaningful improvements in responses that approached normative values or PROs over 12 weeks (Genovese, Fleischmann, et al, 2018; Strand, Schiff, et al, 2018). Therefore, upadacitinib treatment in RA subjects with poor response to either csDMARDs or bDMARDs exhibited favorable effects compared with patients receiving placebo (FitzGerald et al, 2018; van Vollenhoven et al, 2018). An open‐label extension study also demonstrated that efficacy responses last up to 72 weeks in RA patients on 6 mg BID upadacitinib (Genovese, Kremer, Zhong, & Friedman, 2018).…”
Section: Clinical Developmentsmentioning
confidence: 99%